Sosialisasi dan Pelatihan Pemanfaatan TOGA Menjadi Minuman untuk Meningkatkan Imunitas Masyarakat Desa Ploso - Alpandari, Heny; Anwar, Khairul; Krestiani, Veronica; Suharijanto, Suharijanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The immunity of Ploso Village residents is experiencing a decline, marked by increasing complaints of fever, dizziness and flu as a result of the current transition. Based on this, this service is carried out to utilize TOGA which has been planted by residents in their yards into a drink that can increase the body's immunity because it contains antioxidant compounds. This activity was carried out in Ploso Village in February-March 2024. Using socialization, discussion, practice and evaluation methods. Participants who took part in this training were women from PKK Prima Sejahtera. The results of this activity are 1) Participants understand that the bioactive compounds found in several plants can be used as drinks/wedang to increase the body's immunity. 2) Participants can make spiced wedang from TOGA grown in their yard. 3) Participants are very enthusiastic about this service activity.